Cloud Computing Technology and Its Development in the Last 20 Years: Trends, Challenges, and Future Directions - Awaluddin, Muhammad; Windiarti, Ika Safitri (Lembaga Jurnal dan Publikasi Universitas Muhammadiyah Buton, 2025)
Cloud computing has significantly transformed the IT landscape over the past two decades, evolving from basic virtualization technology into a sophisticated, multi-layered ecosystem that serves as the backbone of modern digital infrastructure. This research examines the progression of cloud computing from 2003 to the present, highlighting key technological advancements such as virtualization, containerization, artificial intelligence (AI), and edge computing. The study also addresses major challenges within the cloud computing realm, including security, data sovereignty, and environmental concerns, which continue to impact the evolution of cloud services. Furthermore, it explores emerging trends like quantum computing, 5G integration, and green cloud initiatives, all of which are poised to influence the future of the cloud industry. This paper underscores the transformative role of cloud technology in delivering scalable and cost- effective solutions for businesses, while also emphasizing the necessity of addressing security and sustainability issues to ensure its long-term viability. Through a comprehensive review of current and future advancements in cloud computing, this research enhances our understanding of the critical factors driving cloud adoption, the ongoing challenges it faces, and its potential to foster a sustainable digital ecosystem.